ChemInform Abstract: An Iron(III) Catalyst with Unusually Broad Substrate Scope in Regioselective Alkylation of Diols and Polyols. Issue 27 (16th June 2016) - Ren, Bo; Ramstroem, Olof; Zhang, Qiang; Ge, Jiantao; Dong, Hai
Abstract: The new selective monoalkylation reaction of diverse 1, 2‐ and 1, 3‐diol‐containing structures employs [Fe(dibm)3 ] (dibm = diisobutyrylmethane) as catalyst.